Social-Philosophical Interpretation Of The Concept Of Demographic Growth (Eurasian Journal of Learning and Academic Teaching, 2026)
This article analyzes the concept of demographic growth from a socio-philosophical perspective. Demographic growth is interpreted not only as a quantitative indicator but also as a significant factor reflecting the social quality, cultural values, and historical development of society. The ontological, epistemological, and axiological aspects of demographic growth are examined, along with its relationship to social reproduction, intergenerational continuity, and sustainable development. The study also considers demographic processes in both global and national contexts. The article provides a theoretical and methodological foundation for PhD-level research.